Recombinant human mannose‐binding lectin dampens human alveolar macrophage inflammatory responses to influenza A virus in vitro. Issue 5 (7th January 2014) - Nelson, Benjamin; Zhou, Xiuqin; White, Mitchell; Hartshorn, Kevan; Takahashi, Kazue; Kinane, T. Bernard; Anandaiah, Asha; Koziel, Henry
Abstract : RhMBL may significantly down modulate human alveolar macrophage inflammatory responses to rhMBL‐opsonized IAV, which may limit lung damage. Abstract : IAV pneumonia remains a serious global health problem, and preventative and therapeutic strategies remain limited. AM are critical effector cells in the control of influenza, impairing IAV replication, promoting IAV clearance, and promoting efferocytosis and resolution of lung inflammation. MBL, an innate immune pattern recognition molecule, present in the lungs, binds IAV, and plasma MBL deficiency is associated with increased susceptibility to IAV, although the mechanism remains incompletely understood, and the influence of MBL on the IAV‐AM interaction has not been established. In the current study, focusing on human macrophages (U937 cell line and clinically relevant human AM), data demonstrated that unopsonized IAV is readily internalized, induced release of TNF and ROS, and promoted macrophage apoptosis. In contrast, IAV, opsonized with rhMBL, reduced IAV uptake and macrophage apoptosis and dramatically reduced TNF release and ROS. Macrophage host‐defense responses were reduced further in the presence of MASPs. Taken together, these data support the concept that rhMBL may serve a protective innate host response and a critical biological response modifier function by limiting AM inflammation, oxidative injury, and AM apoptosis, which may allow effective IAV clearance while limiting collateral damage to vital organs, such as the lungs.